The Re-creation of the World: Filming Faith - Plate, S. Brent (Dialog, 2003)
This essay is about the connection of two worlds: the world “out there,” and the re-created world seen on screen and experienced through religious myth and ritual. It is about the similarity between the way films are constructed and the way religious practices are constructed. Film and religion each begin with space and time, but re-create both: Film does this through cinematography, mise-en-scene, and editing, while religions achieve this by setting apart particular objects and periods of time, through the telling of stories, and the gathering together of people focused on a common object, text, or image. The hypothesis here is that by paying attention to the ways films are constructed, we can shed light on the ways religious myths and rituals are constructed, and vice versa.